Cordyceps militaris Exerts Anticancer Effect on Non–Small Cell Lung Cancer by Inhibiting Hedgehog Signaling via Suppression of TCTN3. (May 2020) - Jo, Eunbi; Jang, Hyun-Jin; Shen, Lei; Yang, Kyeong Eun; Jang, Min Su; Huh, Yang Hoon; Yoo, Hwa-Seung; Park, Junsoo; Jang, Ik Soon; Park, Soo Jung
This study aimed to investigate the effect of Cordyceps militaris extract on the proliferation and apoptosis of non–small cell lung cancer (NSCLC) cells and determine the underlying mechanisms. We performed a CCK-8 assay to detect cell proliferation, detection of morphological changes through transmission electron microscopy (TEM), annexin V–FITC/PI double staining to analyze apoptosis, and immunoblotting to measure the protein expression of apoptosis and hedgehog signaling–related proteins, with C militaris treated NSCLC cells. In this study, we first found that C militaris reduced the viability and induced morphological disruption in NSCLC cells. The gene expression profiles indicated a reprogramming pattern of genes and transcription factors associated with the action of TCTN3 on NSCLC cells. We also confirmed that the C militaris –induced inhibition of TCTN3 expression affected the hedgehog signaling pathway. Immunoblotting indicated that C militaris –mediated TCTN3 downregulation induced apoptosis in NSCLC cells, involved in the serial activation of caspases. Moreover, we demonstrated that the C militaris negatively modulated GLI1 transcriptional activity by suppressing SMO/PTCH1 signaling, which affects the intrinsic apoptotic pathway. When hedgehog binds to the PTCH1, SMO dissociates from PTCH1 inhibition at cilia. As a result, the active GLI1 translocates to the nucleus. C militaris clearly suppressed GLI1 nuclear translocation, leading to Bcl-2 and Bcl-xL down-regulation. These results suggested that C militaris induced NSCLC cell apoptosis, possibly through the downregulation of SMO/PTCH1 signaling and GLI1 activation via inhibition of TCTN3. Taken together, our findings provide new insights into the treatment of NSCLC using C militaris .